Premarital pregnancy experiences: Profile of young mothers in women shelters - Hillaluddin, Azlin Hilma (2013)
Premarital pregnancy is a highly stigmatized phenomenon and may possibly be traumatic as well. However, there are adolescents and young adults who continue to commit premarital sex.The high likelihood of unwanted pregnancy will remain a serious concern in the Malaysian society which could lead to further psychosocial problems such as baby dumping, mental health problems, and health concerns among others.Despite experiencing the trauma and stigma of being pregnant and unmarried, there are teenagers and young women who decide to carry on with the pregnancy.This research seeks to examine the experiences of unmarried teenagers and young women who choose to continue their pregnancy while seeking protection in women’s shelters.The highlight of this paper is the profile of young mothers who sought protection in five women shelters throughout the country. The findings suggest disturbing information regarding sexual experience of young girls such as the early age of first sexual encounter, abortion attempt, the usage (non-usage) of contraception and the influence of the social circle environment.